Histopathological and immunohistochemical features of asymptomatic hyperplastic colon polyps - Pospishil , Yu.O.; Varyvoda , O.Yu.; Chelpanova , I.V.; Gavrilyuk , O.M.; Pankevych , L.V. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. Timely diagnosis of precancerous conditions and early colon cancer is important, because colorectal cancer ranks second among women and third among men in the structure of oncological pathology. Most colorectal cancers are thought to arise from adenomas. The hyperplastic polyps are benign and considered harmless, and the malignant potential of these colon polyps is still not fully determined. Studies of hyperplastic polyps and the relationship with colorectal cancer are being conducted. Objective: to study the histopathological and immunohistochemical features of hyperplastic polyps with an asymptomatic course for to determine the diagnostic signs of potential precancerous lesions and the risk of malignant transformation of hyperplastic polyps. Methods. Histological, histochemical and immunohistochemical studies of 22 asymptomatic hyperplastic polyps of the colon were carried out. Results. It was established that hyperplastic polyps with an asymptomatic course and increased risk of malignant transformation were characterized by frequent localization in the proximal parts of the large intestine, a topographic change in the proliferation of enterocytes with a shift to the superficial parts, a higher proliferative activity of enterocytes (Ki-67 of the upper part of the crypt - 24.2±5.5%, the lower part - 30.8+10.3%, ratio of Ki-67 indices=0.82±0.18, (p<0.05)), increased secretion of mucus and manifestations of microsatellite instability with loss of expression of genes of the unpaired nucleotide repair system (loss of expression of the MSH-6 protein (2.14±0.30), which is an unfavorable prognostic sign. Conclusion: The study of structural features and the identification of biomarkers for hyperplastic polyps, which are particularly prone to malignant transformation, will allow to selectively target to patients who have a significantly increased risk of malignancy transformation of hyperplastic polyps based on determination of Ki-67 expression level and immunohistochemical determination of mismatch repair (MMR) protein expression.